Pengaruh Penerapan Tata Tertib Terhadap Tingkat Kedisiplinan Santri Kelas Xii Di Kmi Pondok Pesantren Al-Ishlah Bondowoso - Mutalib, Wahyudi; Nahrawi, Mohammad; Mujahidin, Ahmad; Prasetiya, Benny (Educational Research Center, 2026)
This study aims to analyze the effect of the implementation of institutional rules on the level of student discipline at Kulliyatul Muballighien Al-Islamiyyah (KMI), Al-Ishlah Islamic Boarding School, Bondowoso. Field observations indicate a 10% decrease in students’ compliance with pesantren regulations compared to the previous year, suggesting a gap between the ideal values of pesantren education and actual student behavior. Based on B.F. Skinner’s behaviorism theory and Travis Hirschi’s social control theory, institutional rules in pesantren are viewed as instruments of behavioral reinforcement and social control that play a role in shaping student discipline through mechanisms of reinforcement and the internalization of moral values. This study employed a quantitative approach with an explanatory research design, involving a population of 98 twelfth-grade students selected using total sampling. Data were collected through a five-point Likert-scale questionnaire and analyzed using SPSS version 27 through normality tests, linearity tests, and linear regression analysis. The results showed that the implementation of institutional rules had a significant effect on the level of student discipline, with an F value of 55.099 and a significance level of 0.000 (p < 0.05). This indicates that the better the implementation of institutional rules, the higher the level of student discipline. Theoretically, these findings strengthen the concept that institutional rules function as a means of character building and social control within the Islamic education system. Practically, this study provides important implications for pesantren management, suggesting that institutional rules should not merely serve as supervisory tools but also function as a medium for internalizing values of discipline, responsibility, and moral awareness among students.